Job Stress Analysis for Lathe Machine Operator Based on Human Physiological Feedbacks - Lukodono, Rio Prasetyo; Efranto, Remba Yanuar; Ardianwiliandri, Raditya; Latifani, Olivia; Choiriyah, Miftakhul (Jurnal Ilmiah Teknik Industri, 2023)
Job stress is a circumstance that every employee could faces in performing their job. They tend to deal with it differently according to their own way. It is basically a mismatch between the individual capabilities and organizational demand. The existing employees must exert their ability to complete their tasks in order to fulfilling the organization’s demand. One of the major sources of job stress is excessive workload. Every workload received by employee must fit and balanced with the physical and mental abilities of the employee so that there will be less fatigue and stress that could affect the employee’s performance. This study aims to evaluate the workload for the human physiological feedback. The physiological feedback was evaluated based on the activity while operator using lathe machine. The physiological feedback is based on integumentary activities and cardiovascular activities. The results of this research showed that the operators of the lathe machine operator physiological feedbacks has significant correlation with the Galvanic skin response (GSR). All of indicators such as Heart rate (HR), systole, diastole, and body temperature has positive correlation with the GSR values. Moreover, for noise indicators also has positive correlation with the GSR. This mean that the enviromental condition which represented by noise evaluation has significant correlation with the stress.